MODEL PENDIDIKAN ISLAM BAGI ANAK ANAK DI LINGKUNGAN LOKALISASI - Siti Munfiatik (Al-Rabwah, 2019)
Social environment is one of the factors that can affect a person or group of people to be able to perform an action as well as changes in the behavior of each individual. The social environment we know is the family, the school, and the community environment. It is the duty and role of parents to guide and direct the child to be better. Educational institutions are also responsible for making the personality of children with good character, knowledge and skills. This is expected when they are in the community can adjust to the sociocultural of existing society and are not easily shaken by the changing times, as the second parents in a school, of cours, a teacher must know the model of Islamic education that appropriate used for children especially live in prostitusion area and of course, this children must be different from the children grow in normal environment.